Buprenorphine requires concomitant activation of NOP and MOP receptors to reduce cocaine consumption. (21st June 2017) - Kallupi, Marsida; Shen, Qianwei; de Guglielmo, Giordano; Yasuda, Dennis; Journigan, V. Blair; Zaveri, Nurulain T.; Ciccocioppo, Roberto
Abstract: Buprenorphine's clinical use is approved for the treatment of heroin addiction; however, evidence supporting its efficacy in cocaine abuse also exists. While for heroin it has been demonstrated that the effect of buprenorphine is mediated by its ability to activate μ‐opioid peptide receptor (MOP) receptors, the mechanism through which it attenuates cocaine intake remains elusive. We explored this mechanism using operant models where rodents were trained to chronically self‐administer cocaine for 2 hours daily. Buprenorphine (0.3, 1.0 and 3.0 mg/kg) given intraperitoneally 90 minutes before access to cocaine significantly and dose dependently reduced its intake. Pre‐treatment with naltrexone or with the selective nociceptin/orphanin FQ peptide (NOP) antagonist SB‐612111 did not prevent buprenorphine‐induced reduction of cocaine intake. However, when naltrexone and SB‐612111 were combined, the effect of buprenorphine on cocaine was completely prevented. To confirm that co‐activation of MOP and NOP receptors is the underlying mechanism through which buprenorphine reduces cocaine intake, three compounds, namely, AT‐034, AT‐201 and AT‐202, with a range of affinity and intrinsic activity profiles for MOP and NOP receptors, but weak ability for kappa‐opioid peptide receptor (KOP) transmission, were tested. Consistent with our hypothesis based on buprenorphine's effects, results demonstrated that AT‐034 and AT‐201, which co‐activate MOP and NOP receptors, reduced cocaine self‐administration like buprenorphine. AT‐202, which selectively stimulates NOP receptors, was not effective. Together, these data demonstrate that for buprenorphine, co‐activation of MOP and NOP receptors is essential to reduce cocaine consumption. These results open new vistas on the treatment of cocaine addiction by developing compounds with mixed MOP/NOP agonist properties. Abstract : Buprenorphine, at all doses tested, reduced significantly, in a dose‐dependent manner, the number of cocaine rewards. However, treatment with the combination (SB‐612111 30.0 mg + Nltx 2.5 mg) completely prevented the reduction of cocaine self‐administration by buprenorphine.